How black female teachers negotiate their identities as both union members and practicing teachers: a case study - Hlungwane, Andisiwe Nonzame Rosemond (My University, 2016)
This study considers black female teachers’ conceptions of themselves, their ‘identities’ as teachers and ways in which they negotiate this in relation to their membership in teacher trade unions. Drawing upon Wenger’s model of identity in practice, and recent research into identity construction and teacher activity in trade unions. The study uses a qualitative case study methodology. It uses semi-structured interviews with four Mpumalanga teachers from SADTU and NAPTOSA, within each trade union the study looked at a representative and an ordinary member of the trade union. A major finding of the study was that black female teachers partake in the reconciliation of their various identities, by filtering out what they deemed inappropriate and remaining with those identities which they felt led to less tensions with their teacher identity. It was also found that ordinary members of unions are disengaged with their union identity and therefore do little identity work to reconcile their union and teacher identities. The implications of this for teachers and education in South Africa are discussed. The study calls for further research that explores the process teachers undergo to take ownership of their union identity and therefore develop a sense of agency.
Submitted in partial fulfilment of a Degree of Master in Education Wits School of Education, Curriculum Studies University of the Witwatersrand, South Africa 2016
Keywords: Teachers, Black--South Africa; Women teachers--South Africa; Teachers' unions--South Africa